S74 Endoplasmic stress is associated with fibrosis in interstitial lung disease. (15th November 2017) - Parfrey, H; Moseley, E; Beardsley, B; Knight, J; Marciniak, SJ; Rassl, D
Abstract : Interstitial lung diseases (ILD) are a heterogeneous group characterised by variable amounts of inflammation and fibrosis. However, the development of pulmonary fibrosis is associated with a poorer prognosis. Although distinct histological features differentiate between the ILDs, it is unknown if there are shared pathogenic mechanisms involved in the development of fibrosis. Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of familial and sporadic idiopathic pulmonary fibrosis (IPF). In response to ER stress, cells trigger the unfolded protein response (UPR) and upregulate chaperones, such as BiP, and the phosphatase GADD34, which can regulate epithelial to mesenchyme transition, cell proliferation, apoptosis and cell survival. Aims: We hypothesise that ER stress may be involved in the pathogenesis of fibrosis in all interstitial lung diseases. Methods: Paraffin embedded sections, obtained from video assisted thoracoscopic diagnostic lung biopsies, from 8 patients with familial pulmonary fibrosis, 11 sporadic idiopathic pulmonary fibrosis (IPF), 12 non-specific interstitial pneumonia (NSIP) and 10 hypersensitivity pneumonitis (HP) were evaluated for BiP and GADD34 by immunohistochemistry. Using light microscopy, 6 high power fields were scored for fibrosis, inflammation, BiP and GADD34 using semi-quantitative analysis by 2 blinded, independent investigators. Data were analysed by linear regression using Prism software. Results: Of the 41 biopsy samples analysed, 20 (49%) were non-smokers and 18 (44%) were male. BiP and GADD34 were localised to reactive type II pneumocytes and columnar epithelium within areas of fibrosis. GADD34 was also evident in the endothelium. No staining was detected within fibroblasts or fibroblastic foci. Epithelial GADD34 correlated with extent of fibrosis in familial pulmonary fibrosis (r 2 =0.72 p<0.001), IPF (r 2 =0.51 p<0.0001) and NSIP (r 2 =0.46 p<0.0001). In contrast, BiP was associated with fibrosis in IPF (r 2 =0.49 p<0.0001) and HP (r 2 =0.59 p<0.0001). There was no association with inflammation. Conclusion: These data show that ER stress and the UPR are associated with fibrotic ILDs. Hence targeting ER stress may be a novel therapeutic option for pulmonary fibrosis. Work is on going to identify a peripheral biomarker signature for ER stress.